PERSENTASE KARKAS DAN LEMAK ABDOMEN BROILER YANG DIBERI PAKAN KOMBINASI HERBAL DENGAN MINERAL ZINK - Regar, Mursye N.; Kowel, Youdhie H.S.; Waani, Merci R. (ZOOTEC, 2019)
CARCASS AND ABDOMEN FAT PERCENTAGES IN BROILERS FED RATION COMBINED WITH HERBAL DAN ZINC MINERAL Study was done to evaluate carcass quality of broilers fed ration combined with herbal and zinc mineral. Hundred broilers were randomly divided into four treatments with five replications in each treatment. Each unit was placed five day old chicks. Treatments were consisted of basal ration (R1), basal ration added with 1.5 % of turmeric and 180 ppm of Zinc (R2), basal ration added with 2.5 % of white onion and 180 ppm of Zinc (R3), and basal ration added with anti biotic (R4). Results showed that combination of herbal and zinc mineral affected significantly the carcass and abdomen fat in broilers.Â  Therefore, it can be concluded that combinations of turmeric or white onion and zinc mineral produced ideal carcass and abdomen fat in broilers.Â Key Words: Abdomen fat, broiler, carcass, herbal, zinc.